2021
DOI: 10.1007/s00441-021-03445-4
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-mediated signaling is a master regulator of transcription factors in bovine granulosa cells under oxidative stress condition

Abstract: Transcription factors (TFs) are known to be involved in regulating the expression of several classes of genes during folliculogenesis. However, the regulatory role of TFs during oxidative stress (OS) is not fully understood. The current study was aimed to investigate the regulation of the TFs in bovine granulosa cells (bGCs) during exposure to OS induced by H2O2 in vitro. For this, bGCs derived from ovarian follicles were cultured in vitro till their confluency and then treated with H2O2 for 40 min. Twenty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This finding indicates that NRF2 plays a crucial role in regulating the embryo's response to adverse culture conditions. Previous studies involving bovine granulosa cells and embryos have also suggested that NRF2 function is primarily required under stressful conditions 33 , 37 . Moreover, various molecules with protective roles in cultured cells, including retinal epithelial cells 57 and podocytes 58 , appears to exert their effects through the activation of NRF2, although the underlying molecular pathways have yet to be fully characterized.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding indicates that NRF2 plays a crucial role in regulating the embryo's response to adverse culture conditions. Previous studies involving bovine granulosa cells and embryos have also suggested that NRF2 function is primarily required under stressful conditions 33 , 37 . Moreover, various molecules with protective roles in cultured cells, including retinal epithelial cells 57 and podocytes 58 , appears to exert their effects through the activation of NRF2, although the underlying molecular pathways have yet to be fully characterized.…”
Section: Discussionmentioning
confidence: 94%
“…NRF2 is a master regulator of oxidative balance and plays various cellular roles in regulating redox homeostasis, mitochondrial function, oxidative phosphorylation, ATP production, and fatty acid oxidation 32 . NRF2 has been shown to regulate oxidative stress in granulosa cells under stressful conditions 33 , and this function may involve interactions with miRNAs 34 . Furthermore, NRF2 induces peroxisomal activities in porcine oocytes and embryos 31 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Nrf2 is a transcription factor and when cells are subjected to oxidative stress, Nrf2 is transferred from the cytoplasm to the nucleus and binds to antioxidant response element to promote the transcription of a series of antioxidant genes, such as the GR and SOD genes, which enhances the antioxidant capacity of cells. 21 Under oxidative stress conditions, FOXO protein activity is activated and promotes the expression of a series of antioxidant response genes, such as SOD and glutathione peroxidase (GPX). 22 In breast cancer cells, mitochondrial signal transducer and activator of transcription 3 plays a role in regulating cellular redox balance by regulating antioxidant gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH1 is a DEG in the BPA versus BPS comparison. In the bovine ovary, the NOTCH signalling pathway is involved in follicular development, steroidogenesis and regression of the corpus luteum [64]. This signalling pathway has already been reported to be impacted in the presence of BPA, disrupting juxtacrine communication in rat testes [79] and steroidogenesis in foetal testes in vitro [80].…”
Section: The Expression Of the Lsmem1 And Lif Remained Altered By Bpa...mentioning
confidence: 99%
“…Their effects depend on their concentration and affinity for each receptor, a factor that can partially explain their non-linear effect [63]. Only a few DEG were common between treatment with BPA or BPS and G1, including STAR , a cytoplasmic cholesterol transporter involved in steroidogenesis [3]; SREBF1, a transcription factor involved in the regulation of the biosynthesis of fatty acids and cholesterol [64]; and SPRY2, a negative regulator of tyrosine kinase receptor activity. The mRNA level of these genes in GC was correlated negatively with oocyte developmental competence in bovine [65].…”
Section: Bpa and Bps Do Not Act Predominantly Through Gpermentioning
confidence: 99%